Aerobic and Anaerobic Performances in Tethered Swimming - Papoti, M.; da Silva, A.S. R.; Araujo, G. G.; Santiago, V.; Martins, L.E. B.; Cunha, S. A.; Gobatto, C. A. (International Journal of Sports Medicine, 2013)
The purpose of this study was to investigate whether the critical force (CritF) and anaerobic impulse capacity (AIC) – estimated by tethered swimming – reflect the aerobic and anaerobic performance of swimmers. 12 swimmers performed incremental test in tethered swimming to determine lactate anaerobic threshold (AnTLAC), maximal oxygen uptake (  ˙VO2MAX) and force associated with the  ˙VO2MAX (i ˙VO2MAX). The swimmers performed 4 exhaustive (tlim) exercise bouts (100, 110, 120 and 130% i ˙VO2MAX) to compute the CritF and AIC (F vs. 1/tlim model); a 30-s all-out tethered swimming bout to determine their anaerobic fitness (ANF); 100, 200, and 400-m time-trials to determine the swimming performance. CritF (57.09±11.77 N) did not differ from AnTLAC (53.96±11.52 N, (P>0.05) but was significantly lower than i ˙VO2MAX (71.02±8.36 N). In addition, CritF presented significant correlation with AnTLAC (r=0.76; P<0.05) and i ˙VO2MAX (r=0.74; P<0.05). On the other hand, AIC (286.19±54.91 N.s) and ANF (116.10±13.66 N) were significantly correlated (r=0.81, p<0.05). In addition, CritF and AIC presented significant correlations with all time-trials. In summary, this study demonstrates that CritF and AIC can be used to evaluate AnTLAC and ANF and to predict 100, 200, and 400-m free swimming.
Keywords: critical force; anaerobic impulse capacity; tethered swimming